PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN MELALUI METODE BERMAIN KARPET HURUF PADA MURID TUNAGRAHITA RINGAN KELAS DASAR II DI SLB – C YPPLB MAKASSAR - Rini Lestari; Nurazizah Rahmi R (JURNAL ORTO DIDAKTIKA, 2024)
The problem in this research is the low achievement of Indonesian language in the initial reading competence of mildly intellectually disabled students in the second grade of SLB – C YPPLB Makassar.The research question is: How is the initial reading ability of mildly intellectually disabled students in the second grade of SLB C YPPLB Makassar through the implementation of the letter mat playing method. Based on the problem, the research aims to determine the initial reading ability of mildly intellectually disabled students in the second grade of SLB – C YPPLB Makassar through the implementation of the letter mat playing method. This research is a descriptive study, which aims to describe the initial reading ability before and after the use of the letter mat playing method on mildly intellectually disabled students in the second grade of SLB – C YPPLB Makassar. The data collection technique used is a performance test, and the respondents in this study are 3 mildly intellectually disabled students in the second grade of SLB – C YPPLB Makassar. Data analysis technique uses quantitative descriptive analysis. The research results show that there is an increase in the category value, which initially failed to become very good in the results of the initial reading ability of mildly intellectually disabled students in the second grade of SLB – C YPPLB Makassar. This means that this study shows that the initial reading ability of mildly intellectually disabled students in the second grade of SLB – C YPPLB Makassar can be improved through the use of the letter mat playing method.